1996
DOI: 10.1523/jneurosci.16-08-02758.1996
|View full text |Cite
|
Sign up to set email alerts
|

Spinal amino acid release and precipitated withdrawal in rats chronically infused with spinal morphine

Abstract: Glutamate receptors are implicated in the genesis of opioid tolerance and dependence. Factors governing release of amino acids in systems chronically exposed to opiates, however, remain undefined. Using rats, each prepared with a spinal loop dialysis catheter and with a chronic lumbar intrathecal infusion catheter connected to a subcutaneous minipump, the release of amino acids before and during antagonist-precipitated withdrawal in unanesthetized rats was examined. Spinal infusion of morphine (20 nmol/micro l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 54 publications
3
50
1
Order By: Relevance
“…However, the increase was not significant and the authors suggested that EAA might not play a role in morphine tolerance. 14 This discrepancy between their results and ours might be due to differences between cancer pain patients and naïve rats. Alternatively, only a small amount of EAA released after IT morphine infusion in the study by Jhamanda et al may still have resulted in a reduction of morphine's antinociceptive effect.…”
Section: Discussioncontrasting
confidence: 62%
“…However, the increase was not significant and the authors suggested that EAA might not play a role in morphine tolerance. 14 This discrepancy between their results and ours might be due to differences between cancer pain patients and naïve rats. Alternatively, only a small amount of EAA released after IT morphine infusion in the study by Jhamanda et al may still have resulted in a reduction of morphine's antinociceptive effect.…”
Section: Discussioncontrasting
confidence: 62%
“…If this hypothesis were correct, it could be speculated that administration of a high dose (100 mg/kg) of 2-PMPA leads to high concentrations of NAAG that acts as an agonist, rather than an antagonist at NMDA receptors, and thus increases the severity of morphine withdrawal. In support, it should be noted that during opioid withdrawal there is a massive release of glutamate (Rasmussen, 1995;Jhamandas et al, 1996;Sepulveda et al, 1998). The effects of massive glutamate release apparently may not be prevented by NAAG-induced mGluRII stimulation and/or a decrease in glutamate release.…”
Section: Effects Of Gcp II Inhibition On Morphine Dependence/ Withdrawalmentioning
confidence: 96%
“…Adaptive changes following chronic opioid exposure that might underlie physical dependence by altering neuronal excitability and synaptic transmission include a rebound increase in cAMP levels and in expression of certain types of adenylyl cyclase, guanylyl cyclase, PKA, PKG, and cAMP response element binding protein (CREB) (Nestler, 2001;Barrot et al, 2002;ShawLutchman et al, 2002). The regions important in opioid actions include the spinal cord and supraspinal levels (Jhamandas et al, 1996;Bailey and Connor, 2005;Muscoli et al, 2007;Han et al, 2008;Liu et al, 2009a). Despite decades of investigation, the specific cellular and molecular mechanisms underlying opioid actions remain elusive.…”
Section: Introductionmentioning
confidence: 99%